Efektivitas Skema Simplikasi PPh 21 dengan Tarif Efektif Rata-Rata - Ningsih, Sri Setia; Erion, Erion; Widyowati, Lestari Adhi; Sihombing, Novfitri Landong Namora (JAB (Jurnal Akuntansi & Bisnis), 2025)
In order to increase taxpayer compliance in meeting their tax obligations, the TER scheme, which calculates Article 21 income tax deductions using an average effective rate, is anticipated to make it easier and more convenient for taxpayers to do so each tax period. The study's goal is to ascertain how well the TER scheme, which simplifies the Article 21 Income Tax calculation, works to achieve a more effective, efficient, and accountable tax administration in meeting tax obligations in the company the author studied, PT. X Indonesia, which is in the plastics industry. This study employs both primary and secondary data in a qualitative descriptive manner. According to the study's findings, the TER scheme's calculation method differs from that of earlier provisions, which leads to variations in the recognition of Article 21 Income Tax payable. These variations typically result in variations in the suspension of tax obligations during the January–November period, and at the end of the December period, the obligations increase in size following the computation of Article 21 Income Tax for a year in compliance with Article 17 of the Income Tax Law. Keywords: TER Scheme, Income Tax Article 21, Effectiveness